EXPLORING SPATIAL CONTAGION IN SPAIN'S INTERNATIONAL MIGRATION DISTRIBUTION - Maria Hierro (European Regional Science Association (ERSA), 2011)
This paper explores the Spain's international migration distribution (SIMD) for the 1998-2009 period. Beyond a general depiction of the distribution, the study pays special attention to the role played by space and, particularly, to the possibility of geographical contagion effects. For this latter, and using a spatial Markov chain approach, two new measures of positive and negative contagion are proposed. The results do identify space as key determinant of the SIMD. Furthermore, results reveal that there are contagion effects, positive contagion among provinces surrounded by high-immigration provinces being the most significant.
Keywords: 330